Peran Kepemimpinan Sekolah dalam Mengatasi Konflik Antar Guru dan Dampaknya terhadap Kinerja Institusi. (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
The purpose of this study is to examine how school leadership can resolve teacher conflicts and how this affects educational institutions' overall performance. In the school setting, teacher conflict is frequently inevitable and can negatively affect the collaborative environment, work climate, and attainment of educational objectives. It is crucial for school leadership to mediate, manage, and resolve disputes so that they don't degrade the overall performance of the organization. This study examines numerous theories and empirical research on school leadership, conflict resolution techniques, and their effects on output and workplace culture using a qualitative approach and literature study methodologies. The study's findings demonstrate the importance of effective leadership philosophies like transformational and participative leadership in reducing the likelihood of conflict escalation and fostering productive working relationships. Furthermore, effective dispute resolution can boost the institution's reputation, enhance instructor effectiveness, and establish a positive learning environment. According to this study, school principals should possess both strong managerial abilities and interpersonal skills that enable them to facilitate productive dispute resolution.